THE FUNCTION OF LANGUAGE IN STUDENT INTERACTION AT SCHOOL - Muhammad Ridho Adiputra; Neviyarni (Yayasan Citra Dharma Cindekia, 2021)
Language is a symbolic giving which is a combination of various sentences or syllables in accordance with certain provisions or rules. This very basic part of language is the phoneme or the smallest unit of the language, namely the sounds produced by human tools that are significant in distinguishing meaning through the sounds produced, this makes language a very basic and essential thing in human life. Humans are social creatures who need to interact, and need to communicate with other humans. In order for interaction to take place interactively and well, of course it requires tools, means or media, and the most important thing used by humans to interact is language. In which there are still many students or students who are still unable to interpret or adjust to the meaning of the language, whether in a state of anger, pleasure or also in ordering or ordering and that's all there are still many of these students are not able to properly understand whether it is intended for the development of these students and their environment.